THE THEORETICAL CRITERIA ON THE VAPORIZATION AND COMBUSTION RATES OF EMULSIONS WATER IN HEAVY FUEL OIL - Corneliu MOROIANU (Fiabilitate şi Durabilitate)
The vaporization and combustion characteristics of a heavy oil-water emulsion droplet are investigated with graphological method. The combustion graphology of fuel oils is defined as a new technical and scientific field which deals with the graphic transposition of the processes of fuels combustion development in a simulator. Thus, it is easy to establish the ignition-combustion characteristics, including the laws that govern their changes depending on the combustion conditions and fuel specifications